The prospects of international trade regulation from fragmentation to coherence - Cottier, Thomas; Delimatsis, Panagiotis (Cambridge University Press, 2011)
"For a long time, the GATT led a life of its own as a self-contained regime. The evolution from tariff to non-tariff barriers brought about increasing overlaps with other regulatory areas. WTO rules increasingly interface with other areas of law and policy, including environmental protection, agricultural policies, labour standards, investment, human rights and regional integration. Against this backdrop, this book examines fragmentation in international trade regulation across a wide array of regulatory fields. To this end, it uses a conceptually coherent theoretical framework which is based on the effort to bring about greater coherence among different policy goals and fields, and thus to embed the multilateral trading system within the broader framework of international economics, law and relations. It will appeal to those interested in a forward-looking discussion of the most pressing issues of the international trade agenda"--